Recent nanobiotechnological advancements in lignocellulosic biomass valorization: A review. (1st November 2021) - Roy, Sharmili; Dikshit, Pritam Kumar; Sherpa, Knawang Chhunji; Singh, Anshu; Jacob, Samuel; Chandra Rajak, Rajiv
Abstract: Increase in human population, rapid industrialization, excessive utilization of fossil fuel utilization and anthropogenic activities have caused serious threats to the environment in terms of greenhouse gas emissions (GHGs), global warming, air pollution, acid rain, etc. This destruction in sustainability can be averted by a paradigm shift in the fuel production from fossil resources to bioenergy. Amongst different forms of bioenergy, lignocellulosic biomass can be utilized as an attractive substrate for the production of several high-value products owing to its renewability, easy availability, and abundance. Additionally, utilization of these waste biomasses reduces the environmental hazards associated with its disposal. Impedance of lignin and crystalline nature of cellulose pose major bottlenecks in biomass based energy. Though, several physio-chemicals processes are recommended as mitigation route but none of them seems to be promising for large scale application. In recent years, a right fusion of biological treatment combined with nanotechnology for efficient pretreatment and subsequent hydrolysis of biomass by ubiquitous enzymes seems to be promising alternative. In addition, to overcome these difficulties, nanotechnology-based methods have been recently adopted in catalytic valorization of lignocellulosic biomass. The present review has critically discussed the application of nano-biotechnology in lignocellulosic biomass valorization in terms of pretreatment and hydrolysis. A detailed discussion on the application of various nanoparticles in these processes, enzyme immobilization and end-production utilization is presented in this review. Finally, the review emphasizes the major challenges of this process along with different routes and recommendations to address the issues. Graphical abstract: Image 1 Highlights: Lignocellulosic materials act as potential biomass resource for valorization. Nanomaterials and tailored enzymes contribute the most for this process. Broad range of applications of various nanobiocatalysts for biomass hydrolysis. Major end products are lignin, lignin degraded intermediates and sugars. Prominent role of nanomaterials for biomass valorization in circular bioeconomy.